1997
DOI: 10.1108/02621719710174525
|View full text |Cite
|
Sign up to set email alerts
|

The effect of personality type on team performance

Abstract: Team approach to IS developmentThe development of innovative solutions to complex problems has become increasingly challenging. The modern information systems (IS) development model includes the use of cross-functional teams, which comprise both users, such as accountants and salespeople, and IS professionals such as systems analysts and programmers. Team members must work together effectively to produce successful systems. In the past, IS departments perceived themselves as autonomous units that provided spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
110
0
11

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(126 citation statements)
references
References 17 publications
5
110
0
11
Order By: Relevance
“…He found that project grade was predicted by extraversion, an analytical disposition, and a lifestyle that values structure and order. Several other studies support this work and suggest that there is a degree of congruence between the personalities of systems analysts (or designers) and end users (Bradley, 1997;Kaiser & Bostrom, 1982).…”
Section: Predictors Of Ict Career Success In a Changing Workplacesupporting
confidence: 55%
“…He found that project grade was predicted by extraversion, an analytical disposition, and a lifestyle that values structure and order. Several other studies support this work and suggest that there is a degree of congruence between the personalities of systems analysts (or designers) and end users (Bradley, 1997;Kaiser & Bostrom, 1982).…”
Section: Predictors Of Ict Career Success In a Changing Workplacesupporting
confidence: 55%
“…Taking into account results of this assessment, groups were formed that included a variety of introverted and extroverted students as heterogeneous teams are more successful than homogeneous teams. [25][26][27] For example, a team with extroverted and introverted members sees benefits in the team's attitude. 28 By organizing groups based on these personality traits, differing perspectives and work methods were accounted for in each student group.…”
Section: Methodsmentioning
confidence: 99%
“…Among his major theoretical contributions was the proposal that there are three main components to human personality, namely the 'id' (the primary source of psychic energy and motivation that works on the pleasure principle, seeking immediate gratification of instinctive needs), the 'ego' (operating on the reality principle, attempting to control the 'id' by postponing action until the desired object can be achieved) and the 'super ego' (developed by socialization in childhood and the moral or judicial branch of personality, enforcing control over the 'ego' by rewards and punishments such as anxiety and depression). Although the impact of Freudian theory on occupational assessment is viewed as very limited, Jung for example, was able to develop measures of personality based on the psychoanalytical theories of personality (Greenspan & Pollock, 1997 (Bradley and Hebert, 1997;Fitzgerald, 1997;Kaplan and Sacuzzo, 2001). …”
Section: The Psychoanalytic Approach To Personalitymentioning
confidence: 99%